Parental, gestational, and early-life exposure to indoor environmental hazardous factors on allergic rhinitis among preschool children in Urumqi City: a case-control study - Tingting Wang; Haonan Shi; Huizhen Qi; Lan Jiang; Yuting Lin; Jian Yao; Junwen Lu; Qi Yan; Aiyong Zhu; Xuan Yao (Jornal de Pediatria, 2023)
Objective: Allergic rhinitis (AR) is a disease associated with impaired quality of life and heredity. This study aimed to investigate the association of allergic rhinitis in preschool children with exposure to indoor environment-related factors early in life. Methods: In August 2019, the authors implemented a study among 2020 preschool children in Urumqi City using a case-control design. The study included parental reports for the occurrence of AR in children, parental history of respiratory disease, and indoor environmental correlates of maternal exposure from 1 year prior to pregnancy until the child's age of 0-1 year. Results: Mode of birth (cesarean section) (OR = 1.31, 95% CI = 1.02∼1.67), father with AR (OR = 2.67, 95% CI = 2.08∼3.44), mother with AR (OR = 3.70, 95% CI = 2.88∼4.74), mother with asthma (OR = 3.11, 95% CI = 1.18∼8.20), and mother with newly purchased furniture in the parents' residence during pregnancy (OR = 1.49, 95% CI = 1.03∼2.14) were risk factors for AR in children. Conclusions: The focus of allergic rhinitis should be on children with a family history of AR and asthma and cesarean delivery. Primary prevention efforts for AR in preschool children are avoiding exposure of children to indoor environmental hazardous factors early in life.